PROTOTYPE TEMPAT PEMROSESAN AKHIR SAMPAH (TPAS) APUNG DI DESA UJUNGALANG KECAMATAN KAMPUNGLAUT - Agus Darwanto; Kis Rindiana Subroto; Kusumaning Tyas Fudiana (Jurnal Inovasi Daerah, 2022)
Kampunglaut Subdistrict has a unique geographical shape resembling an archipelago, causing problems around waste management. Residents prefer to dispose of their household waste directly into the waters of the mangrove forest, thereby creating a risk of flooding during high tides and silting of the waters of the Segara Anakan lagoon. This study aims to design a prototype of the appropriate floating waste final processing site for the Kampunglaut area and measure the level of acceptance of the Kampunglaut residents towards the design of the floating waste final processing site. The research was carried out by making a prototype of the final floating waste processing site and conducting simulation tests on the Serayu River and in Lempongpucung Hamlet, Ujungalang Village, Kampunglaut District, then conducting discussions with the apparatus and residents of Ujungalang Village, Kampunglaut District, Dinas Lingkungan Hidup (DLH) of Cilacap Regency and Cilacap State Polytechnic (PNC). The Floating Final Waste Processing Site (TPAS) is made by combining a plastic bowl with a nylon net that is spaced with steinless wire and then placing a tire as a float between the plastic bowl and a nylon net. The bowl is designed to open and close using a stainless hinge then an Arduino-based ultrasonic sensor is installed on the ceiling of the bowl. To provide information on the amount of waste generated, the sensor is connected to a cellphone that has the blynk application installed using IoT technology. The response of village officials and residents of Ujungalang was very enthusiastic about the prototype of the floating final waste processing site (TPAS). The existence of the Apung TPAS motivated the residents of Ujungalang Village to immediately form a waste bank unit that will manage the waste that has been collected in the Apung TPAS.